The effectiveness of concept maps based on blended learning in developing the jurisprudential concepts of Non-Native Arabic Learners (NNAL) - Alodaini, Ahmed Mahyoub; Salem, El-Sayed Mohamed (Journal of Educational and Psychological Sciences, 2021)
The aim of the current research is to develop the proposed program in the electronic concept maps based on integrated learning in the development of jurisprudential concepts, and to define the effectiveness of such program for the Non-Native Arabic learners at level three (intermediate).To achieve these aims the researcher prepared a teacher's guide, a student’s book, and a test of jurisprudential concepts for Non-Native Arabic learners.The research model consisted of (21) students, who were selected randomly, and it used the descriptive approach and the quasi-experimental approach, and applied the quasi-experimental design based on one group.The research concluded the following results: A proposed program in the concept maps based on integrated learning in developing jurisprudential concepts for Non-Native Arabic learners, including a teacher's guide and a student book.After completing the experiment, a statistically significant difference was reached, at a level of significance (0.05) between the medium scores of the learners in the two applications: the pre and post.The overall result of the test favoured the post application, and thus, confirms the effectiveness of using the concept maps based on integrated learning in the development of jurisprudential concepts for Non-Native Arabic learners in general, and in light of the results reached, the researcher presented a number of recommendations and suggestions.
Keywords: Non-Native Arabic learners; concept maps; ideas of learning concepts; jurisprudential concepts; Study Students